2020
DOI: 10.1159/000505635
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Toddlers, Preschool Children, and Adolescents

Abstract: <b><i>Background:</i></b> Vitamin D supplementation is known to both prevent and treat rickets, a disease of hypomineralized bone. Childhood is a period of great bone development and, therefore, attention to the vitamin D needed to optimize bone health in childhood is imperative. <b><i>Summary:</i></b> Observational studies have pointed to a vitamin D status, as indicated by a 25-hydroxyvitamin D concentration, of 50 nmol/L to ensure avoidance of rickets and of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 68 publications
3
33
0
1
Order By: Relevance
“…On the one hand, researchers believe vitamin D bioavailability in obese individuals is decreased because of vitamin D deposition in body adipose tissue and altered expression levels of vitamin Dmetabolizing enzymes (2,7,17). Moreover, obese children are less likely to engage in outdoor activities, which results in reduced vitamin D synthesis (21). On the other hand, studies found that vitamin D regulated multiple aspects of adipose biology, such as adipogenesis and metabolic and endocrine function of adipose tissues (7).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, researchers believe vitamin D bioavailability in obese individuals is decreased because of vitamin D deposition in body adipose tissue and altered expression levels of vitamin Dmetabolizing enzymes (2,7,17). Moreover, obese children are less likely to engage in outdoor activities, which results in reduced vitamin D synthesis (21). On the other hand, studies found that vitamin D regulated multiple aspects of adipose biology, such as adipogenesis and metabolic and endocrine function of adipose tissues (7).…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal vitamin D status in children is a global health problem (5,14,(58)(59)(60). Due to both skeletal and extra-skeletal functions of vitamin D (61,62), the symptoms of VDD in children could be varied (63) and at the extreme state might be manifested as nutritional rickets (64).…”
Section: Discussionmentioning
confidence: 99%
“…Even subclinical deficiency may adversely affect the child's peak bone mass, cardiometabolic markers and general health later in life (10)(11)(12)(13). Thus, interest in optimization of vitamin D status of children and adolescents is growing in both developed and developing countries (14)(15)(16) and greater emphasis is put on urgent suitable interventions to combat VDD problem (17).…”
Section: What Is Newmentioning
confidence: 99%
“…Moreover, Vitamin A deficiency may alter the intestinal microbiota which may compromise enteric pathogen clearance [38]. Vitamin D is involved in the processes of bone mineralization and growth through the regulation of calcium and phosphorus homeostasis [39]. The main site of Vitamins A and D absorption is small intestine which is the place of EED pathology [40].…”
Section: Discussionmentioning
confidence: 99%